H∞ optimal control of vehicle active suspension systems in two time scales. (3rd April 2021) - Fu, Zhi-Jun; Dong, Xiao-Yang
Abstract : In this paper, a novel H∞ control method in two time scales is proposed for active suspension systems. Two time scales are considered based on the natural time scale separation existing in the active suspension systems, i.e. the sprung mass part corresponding to the fast dynamics and the unsprung mass part corresponding to the slow dynamics. Singular perturbation theory is used to establish a dual time scale active suspension model and design a H∞ controller. Compared with the commonly used H∞ controller, the time-sharing dynamic characteristics make the proposed two time scales H∞ controller have better dynamic response when encountering dynamic road input, so as to better meet the control performance requirements of active suspension. The effectiveness of the proposed H∞ control method in two time scales is illustrated through co-simulations.